Elementary Geometry for College Students (7th Edition) Clone

Published by Cengage
ISBN 10: 978-1-337-61408-5
ISBN 13: 978-1-33761-408-5

Appendix A - A.2 - Formulas and Equations - Exercises - Page 546: 23

Answer

y = -12

Work Step by Step

We multiply both sides by 3: $-y + 3\times 2 = 3\times 6$ $-y +6 = 18$ We add $y$ to both sides and in the meantime we subtract 18. $6-18 = y = -12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.